Penurunan Berat Badan pada Remaja Obesitas Menggunakan Hipnoterapi - Maria Tarisia Rini; Bangun Dwi Hardika; Ketut Suryani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to determine the effect of hypnotherapy on weight loss in obese adolescents. The research design used is a quasi-experiment. The results showed that 15 respondents (68.2%) experienced weight loss, and seven respondents (31.8%) did not experience weight loss from the statistical test results obtained p-value 0.001 with a correlation coefficient value of 0.682. Also, the p-value of the chi-square test results is 0.004. In conclusion, there is a significant relationship between hypnotherapy and weight loss. Keywords: Weight Loss, Hypnotherapy, Youth